(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper examines the remarkable variety, expansiveness, and artistic significance of Radif in the Ghazals of Munir Niazi, one of the most distinctive and influential voices in modern Urdu poetry. Munir Niazi is recognized as the founder of a unique poetic school, whose imaginative vision, symbolic richness, and fresh imagery set him apart from his contemporaries. His Ghazals reflect a harmonious blend of personal experience, social consciousness, and modern sensibility, woven together through a refined and innovative use of Radif. Unlike many poets who employ Radif in a conventional or predictable manner, Munir Niazi transforms this poetic device into a meaningful expressive tool that captures the psychological depth, inner complexity, and philosophical undertones of his verse. The refrains in his Ghazals serve not only as structural embellishments but also as mirrors of his poetic temperament, mood, and worldview. Critics such as Dr. Waqar Ahmad Rizvi and Dr. Anwar Sadeed have acknowledged Munir Niazi’s mastery in creating a mysterious, symbolic, and emotionally resonant poetic atmosphere through his careful choice of words and images. This study highlights how Munir Niazi’s innovative use of Radif enhances the aesthetic and thematic sophistication of his Ghazals, securing his unique place in the modern Urdu literary canon. حوالہ جات 1۔ وقار احمد رضوی ، ڈاکٹر ، تاریخ جدید اردو غزل، اسلام آباد، نیشنل بُک فاؤنڈیشن ، 1988ء ص:911 2۔ ڈاکٹر انور سدید، چہار سو ، راوالپنڈی ، فیض الاسلام پرنٹنگ پریس، ۲۰۰۵،ص :۳۰ 3۔ منیر نیازی، کلیات منیر نیازی، لاہور،ماورا پبلیکیشنز ، ۱۹۸۶، ص:۱۱ 4۔ ایضاً،ص:۲۸ 5۔ ایضاً،ص:۳۵ 6۔ ایضاً،ص:۴۲ 7۔ ایضاً،ص:۵۵ 8۔ ایضاً،ص:۸۳ 9۔ ایضاً،ص:۸۴ 10۔ ایضاً،ص:۴۹ 11۔ ایضاً،ص:۵۵ 12۔ ایضاً،ص:۵۷ 13۔ ایضاً،ص:۵۹ 14۔ ایضاً،ص:۶۲ 15۔ ایضاً،ص:۸۱ 16۔ منیر نیازی ، کلیات منیر ( آغاز زمستاں میں دوبارہ )، لاہور،ماورا پبلیکیشنز ، ۱۹۸۶،ص :۱۲ 17۔ ایضاً،ص:۱۶ 18۔ منیر نیازی ، کلیات منیر ( ساعتِ سیار)، لاہور،ماورا پبلیکیشنز ، ۱۹۸۶،ص:۳۷ 19۔ ایضاً،ص:۴۱ 20۔ منیر نیازی،پہلی بات ہی آخری تھی، لاہور، ماورا پبلیکیشنز، ۱۹۸۶،ص:۴۹ Bibliography: Rizvi, Waqar Ahmad, Dr. (1988). Tareekh-e-Jadeed Urdu Ghazal (The Modern History of Urdu Ghazal). Islamabad: National Book Foundation Sadeed, Anwar, Dr. (2005). Chahar Soo. Rawalpindi: Faiz-ul-Islam Printing Press Niazi, Muneer. (1986). Kulliyat-e-Muneer Niazi. Lahore: Mavara Publications Niazi, Muneer. (1986). Kulliyat-e-Muneer (Aaghaz-e-Zamistan Mein Dobara). Lahore: Mavara Publications Niazi, Muneer. (1986). Kulliyat-e-Muneer (Saa’at-e-Sayyar). Lahore: Mavara Publications Niazi, Muneer. (1986). Pehli Baat Hi Aakhri Thi. Lahore: Mavara Publications